Analysis Qualitative of Bioactive Compounds of Chromolaena odorata Leaves from Aceh Besar District - Tahara Dilla Santi; Aditya Candra (Faculty of Medicine, Universitas Jember, 2023)
Chromolaena odorata leaves have been used by the people of Aceh Besar as herbal medicine. The chemical compounds in the leaves of this plant act as antioxidants, anti-inflammatories, antibacterials and wound healers. The research objective was to determine the phytochemical content of C. odorata leaves through qualitative methods. The extraction method used is maceration and testing of bioactive compounds using a color test. The results showed that the yield percentage was 6.05%. The results of the analysis of phytochemical compounds obtained seven phytochemical compounds contained in C. odorata, namely compounds belonging to the class of flavonoids, phenolics, alkaloids, terpenoids, saponins, steroids and tannins. It is recommended to identify chemical compounds using the GC-MS test to obtain specific compounds that play an active role in anti-inflammatory, antioxidant and antibacterial activities. Keywords: C. odorata, Rendemen, Maceration, Color Test, GC-MS